Objek Deteksi Makanan Khas Palembang Menggunakan Algoritma YOLO (You Only Look Once) - Lusiana Rahma; Hadi Syaputra; A.Haidar Mirza; Susan Dian Purnamasari (Jurnal Nasional Ilmu Komputer, 2021)
Deep learning is a part of machine learning method that uses artificial neural network (ANN). The type of learning in deep learning can be supervised, semi-supervised, and unsupervised [7] . CNN & RNN (Supervised) and RBM & Autoencoder (Unsupervised) are deep learning algorithms. All of the above algorithms have uses in their respective fields, depending on what we want to use them for. One of the most frequently used cases for deep learning is object detection and classification. The Convolutional Neural Network (CNN) algorithm is the most widely used algorithm for object detection cases, one of the reasons because it is supported by Google's Tensorflow framework, but it turns out that there is one object detection algorithm that has a higher level of accuracy and processing speed, namely You Only Look Once (YOLO) which can run on 2 frameworks (Darknet & Darkflow) and is supported by GPU. That's why here the author prefers to do object detection with the You Only Look Once (YOLO) method. The research data with the title Palembang Food Detection Object Using the YOLO (You Only Look Once) Algorithm is a sample photo of food from Google Image. There are 31 types of Palembang specialties, each type consists of approximately 50 to 70 images, so the total images used are from 31 types of Palembang foods, namely 1955 images with jpeg format for training data, and 31 images with jpeg format typical Palembang foods for test data.